Literacy in everyday life : reading and writing in early modern Dutch diaries - Blaak, Jeroen (1972-....; historien) (Egodocuments and history series,, 2009)
"Until recently, historians of reading have concentrated on book ownership and trying to map out a history of who read what. The reading experience has been a subject more difficult to research. As has been pointed out before, egodocuments can be valuable sources in this case. Following this lead, Literacy in Everyday Life focuses upon four early modern Dutch diaries in which readers document their daily life and in which they recount their reading. In the analysis, other ways in which these four readers communicated are also addressed, especially speech and writing. This book therefore provides an insight into the possible uses of literacy and the interaction between the printed, written and spoken word in the early modern Dutch Republic"